TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) DAN UPAYA PENANGGULANGANNYA MELALUI UNDANG UNDANG NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG - Sri Setiawati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
In the independence era, especially in the reformation era that highly appreciates Human Rights, the presence of slavery or servitude issue is no longer tolerated. From the legal point of view, Indonesia has stated that slavery or servitude is a crime against a person's freedom that shall be punished by an imprisonment that ranges between five to fifteen years (Article 324-337 of the Penal Code). However, advancement in information technology, communication, and transportation that has accelerated globalization, is also abused by criminals to disguise the slavery and servitude into their new form: human trafficking; they operate secretly and move outside the law.Traffickers – who quickly have grown into transnational syndicates – are very subtle in trapping their preys, but very cruel in exploiting their preys in various ways so victims are powerless to free themselves. Reinforcement of the commitment made by the Government of the Republic of Indonesia (RI) for the elimination of human trafficking is reflected in Presidential Decree No. 88Year 2002 on the National Plan of Action for the Elimination of Trafficking of Women and Children (RAN P3A) and the Bill on Elimination of the Crime of Human Trafficking (UU PTPPO) in order to be passed as a law. In the 2005-2009 National Legislation Program, the Bill on the Crime of Human Trafficking was ranked number 22, out of 55 priority bills to be deliberated in 2005.Prosecution against traffickers has been intensified by building the capacity of law enforcers and greater cooperation with other stakeholders and law enforcers from friendly countries, so the National Police of the Republic of Indonesia has processed 23 of verdicts from the Court: some were found not guilty, others were sentenced for between 6 months to 13 years in prison; the average punishments were 3 years and 3 months. Information dissemination and advocacy by various parties to law enforcers has led to serious penalties being inflicted upon the traffickers. Indonesia has made progress in the elimination of human trafficking especially in women and children, but it is still far from reaching the goal of National Plan of Actions of Elimination of Trafficking of Women and Children, that is: ”To eliminate all type of trafficking of women and children in Indonesia”. Thus, attempts in strengthening the network should be intensified so that the cruelty against Indonesian women and children can be immediately eliminated.